GATA-1-Mediated Proliferation Arrest during Erythroid Maturation - Rylski, Marcin (American Society for Microbiology, 2003)
Transcription factor GATA-1 is essential for erythroid and megakaryocytic maturation. GATA-1 mutations are associated with hematopoietic precursor proliferation and leukemogenesis, suggesting a role in cell cycle control. While numerous GATA-1 target genes specifying mature hematopoietic phenotypes have been identified, how GATA-1 regulates proliferation remains unknown. We used a complementation assay based on synchronous inducible rescue of GATA-1(−) erythroblasts to show that GATA-1 promotes both erythroid maturation and G(1) cell cycle arrest. Molecular studies combined with microarray transcriptome analysis revealed an extensive GATA-1-regulated program of cell cycle control in which numerous growth inhibitors were upregulated and mitogenic genes were repressed. GATA-1 inhibited expression of cyclin-dependent kinase (Cdk) 6 and cyclin D2 and induced the Cdk inhibitors p18(INK4C) and p27(Kip1) with associated inactivation of all G(1) Cdks. These effects were dependent on GATA-1-mediated repression of the c-myc (Myc) proto-oncogene. GATA-1 inhibited Myc expression within 3 h, and chromatin immunoprecipitation studies indicated that GATA-1 occupies the Myc promoter in vivo, suggesting a direct mechanism for gene repression. Surprisingly, enforced expression of Myc prevented GATA-1-induced cell cycle arrest but had minimal effects on erythroid maturation. Our results illustrate how GATA-1, a lineage-determining transcription factor, coordinates proliferation arrest with cellular maturation through distinct, interrelated genetic programs.